Legacy effect of microplastics on plant–soil feedbacks - Lozano, Yudi M.; Rillig, Matthias C. (Frontiers in Plant Science, 2022)
Microplastics affect plants and soil biota and the processes they drive. However, the legacy effect of microplastics (their role in plant-soil feedback, a key feature in plant-soil interactions), is still unknown. We address this here, using soil from a previous experiment, which has been conditioned with 12 microplastic types. To evaluate the legacy effect of microplastics, we grew a native Daucus carota and a range-expanding plant species Calamagrostis epigejos with inocula extracted from each one of these soils. At harvest, plant biomass and root morphological traits were measured. Films led to positive feedback on shoot mass (higher mass with inoculum from soil conditioned with microplastics than without), likely via negative effects of harmful soil biota. Foams and fragments also caused positive feedback on shoot mass likely via effects on enzymatic activities and mutualistic soil biota. Fibers caused negative feedback on root mass as they may promote the abundance of soil pathogens. Microplastics also had a legacy effect on root traits: Daucus had thicker roots probably for promoting mycorrhizal associations while Calamagrostis had reduced root diameter probably for diminishing pathogenic infection. Microplastic legacy on plants is species-specific and may affect plant biomass primarily via root traits. Microplastics, depending on their shape and polymer type, affect plant-soil feedbacks.